SOME ISSUES OF IMPROVING FAMILY LAW REGULATION (Scientific journal of the Fergana State University, 2023)
As long as the family is protected by the state, it is time to maintain its stability, reduce the number of divorces between spouses, strengthen organizational and legal mechanisms to maintain the integrity and stability of families, increase the effectiveness of reforms in this area. This article analyzes some issues of improving family legislation to preserve family independence. As a result, some suggestions and recommendations for improving family law will be put forward.